The Influence of Brand Image and Price Perception on Customer Loyalty to Apple Smartphones with Customer Satisfaction as Mediation - Diva Aisyah Ardelia; Edy Purwo Saputro (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study examines how pricing perception and brand image affect customer loyalty among Apple smartphone users, with customer satisfaction as a mediating variable. Data was collected from 100 undergraduate students in Surakarta, aged 18 to 25, who have used or owned an Apple smartphone. While this sample provides insights into a specific demographic, it may limit the study's generalizability. Structural Equation Modeling (SEM) with SmartPLS 3 was used to analyze the data. SEM was chosen due to its ability to model complex relationships and examine direct and indirect effects. The results show that brand image positively influences customer satisfaction but does not directly affect loyalty. Price perception significantly impacts satisfaction, which in turn affects loyalty. Customer satisfaction mediates the relationship between price perception, brand image, and loyalty. The study's limitations include the focus on a specific sample, suggesting future research should compare brands and explore factors like customer experience to deepen understanding of loyalty drivers.